The Bible in the Pulpit The Renewal of Bilical Preaching - Keck, Leander E. (Nashville AbiNgdon Press, 1978)
Answers to many questions about the relationship to the pulpit of historical studies & biblical criticism, & illustrates ways to deal with fundamental matters of interpretation.
Keywords: Bible -- Homiletical use. Preaching. Sermons, American. Bible